Single Nucleotide Polymorphism rs6445975 in the PXK Gene Is Correlated with Susceptibility and Clinical Characteristics of Systemic Lupus Erythematosus - Mansour Karimifar; Nafiseh Sereshti; Rasoul Salehi; Maryam Mousavi; Hadi Karimzadeh; Amirhossein Salehi; Bahram Pakzad (Tehran University of Medical Sciences, 2022)
Background: Recently, genome-wide association studies (GWAS) have discovered several single nucleotide polymorphisms (SNPs) and loci associated with the risk of systemic lupus erythematosus (SLE). rs6445975 (T>G; intronic variant) polymorphism in the PXK gene is one of these loci. However, there was an inconsistency between the results of replicative studies on European and Asia ancestry. This study aimed to assess the possible association between rs6445975 polymorphism with SLE risk in the Iranian population. Methods: Genotype and allele distribution of rs6445975 polymorphism were investigated in 110 patients with SLE and 115 healthy controls in Isfahan University of Medical Sciences, Isfahan, Iran in 2019 via real-time PCR high resolution melting method (HRM). Results: GG and TG genotypes, but not TT genotype, were associated with increased risk of SLE (GG vs TT; OR= 7.538; 95%CI [3.47, 17.066] and TG vs TT; OR=2.21; 95%CI [1.06, 4.72]). Inheritance analysis revealed that TG + GG was correlated with the increased risk of SLE disease in the dominant model (OR=3.928; 95%CI [2.056, 7.74]). Moreover, subjects with the G allele were more frequently affected with SLE than individuals with the T allele (OR= 3.55; 95%CI [2.37, 5.36]). The G allele in patients was correlated with serum concentration of CRP, ESR, anti-dsDNA antibody, C3, and C4 and presentation of some clinical manifestations such as kidney involvements and skin lesions (P<0.05). Conclusion: Our findings suggest a substantial association between rs6445975 polymorphism in the PXK gene with susceptibility and clinical characteristics of SLE in the Iranian population.